2019
DOI: 10.1002/ijc.32263
|View full text |Cite
|
Sign up to set email alerts
|

Concordance with the World Cancer Research Fund/American Institute for Cancer Research recommendations for cancer prevention and colorectal cancer risk in Morocco: A large, population‐based case–control study

Abstract: The present study aimed to investigate associations between adherence to the recommendations on cancer prevention from the WCRF/AICR and colorectal cancer (CRC) risk in Morocco. Incident CRC cases (n = 1,516) and controls (n = 1,516) matched on age, sex and center, were recruited between September 2009 and February 2017 at five major hospitals located in Morocco. In‐person interviews were conducted to assess habitual diet using a validated Food Frequency Questionnaire, physical activity and anthropometric meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 40 publications
3
38
0
1
Order By: Relevance
“…In agreement with the results obtained, El Kinany and coworkers [16] found that greater adherence to the 2018 WCRF/AICR score decreased overall CRC risk by 42% after comparing 1516 cases with 1516 controls in Morocco. Similarly, a 24-year-follow-up cohort study [13], with 68,977 women from the Nurses' Health Study and 45,442 men from the Health Professionals Follow-up Study, found a statistically significant inverse association between adherence to the updated WCRF/AICR score and the incidence of CRC risk in men.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In agreement with the results obtained, El Kinany and coworkers [16] found that greater adherence to the 2018 WCRF/AICR score decreased overall CRC risk by 42% after comparing 1516 cases with 1516 controls in Morocco. Similarly, a 24-year-follow-up cohort study [13], with 68,977 women from the Nurses' Health Study and 45,442 men from the Health Professionals Follow-up Study, found a statistically significant inverse association between adherence to the updated WCRF/AICR score and the incidence of CRC risk in men.…”
Section: Discussionsupporting
confidence: 87%
“…Some prospective cohort studies [6,[8][9][10][11][12][13] and case-control studies [14][15][16] have evaluated the associations between CRC risk and adherence to cancer-specific nutritional recommendations with inconsistent results. However, limited longitudinal studies [13,16] have been conducted to assess associations based on the updated 2018 WCRF/AICR recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few reports investigated the association between the 2018 release of the WCRF/AICR recommendations and cancer risk [42,[46][47][48]. The present study is the first evaluating the updated recommendations in the prevention of invasive breast cancer.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, to prevent (or minimize) the inclusion of false controls, all controls were systematically asked questions about their medical history and clinical symptoms related to CRC. A detailed description of the methodology and the study design has previously been published . In summary, 2,906 matched cases–controls pairs aged 18 years or above and matched by age, sex and center were recruited from 2009 to 2017 at the largest five university hospitals located in Rabat, Casablanca, Oujda, Marrakech and Fez.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the methodology and the study design has previously been published. 15,16 In summary, 2,906 matched cases-controls pairs aged 18 years or above and matched by age, sex and center were recruited from 2009 to 2017 at the largest five university hospitals located in Rabat, Casablanca, Oujda, Marrakech and Fez. The informed consent was obtained prior to participation in the study.…”
Section: Designmentioning
confidence: 99%